Pravni ukrepi za zmanjšanje količine zavržene hrane v Evropski uniji - Igličar, Matej (Pravni letopis, 2023)
Food waste is a major factor in sustainable development, with significant social, economic and ecological consequences. In 2020, approximately 127 kilograms of food per capita was wasted in the European Union, with 55% of food waste occurring in households. As EU bodies and institutions have been highlighting the importance of food waste and calling for its reduction for more than a decade, the European Commission has committed itself to setting legally binding targets for reducing food waste by the end of 2023. Following a terminological baseline and an assessment of current food waste, this paper presents legal measures in the areas of aesthetic standards for food, packaging, use-by-date labelling and food donation that can reduce food waste within the existing European legal framework. The European Union has considerable room for improvement within this framework. If it wishes to achieve high-flying goals, bolder actions will be necessary.
Keywords: darovanje hrane; datumi uporabnosti; estetski standardi; Evropska unija; odpadna hrana; pravni ukrepi; trajnostni razvoj; zavržena hrana